Lowering water table reduces carbon sink strength and carbon stocks in northern peatlands - Min Jung Kwon; Ashley Ballantyne; Philippe Ciais; Chunjing Qiu; Elodie Salmon; Nina Raoult; Bertrand Guenet; Mathias Göckede; Eugénie S. Euskirchen; Hannu Nykänen; Edward A. G. Schuur; Merritt R. Turetsky; et al. (Global Change Biology, 2022)
Peatlands at high latitudes have accumulated >400 Pg carbon (C) because saturated soil and cold temperatures suppress C decomposition. This substantial amount of C in Arctic and Boreal peatlands is potentially subject to increased decomposition if the water table (WT) decreases due to climate change, including permafrost thaw‐related drying. Here, we optimize a version of the Organizing Carbon and Hydrology In Dynamic Ecosystems model (ORCHIDEE‐PCH4) using site‐specific observations to investigate changes in CO 2 and CH 4 fluxes as well as C stock responses to an experimentally manipulated decrease of WT at six northern peatlands. The unmanipulated control peatlands, with the WT −2 year −1 ; including 6 ± 7 g C–CH 4 m −2 year −1 emission). We found, however, that lowering the WT by 10 cm reduced the CO 2 sink by 13 ± 15 g C m −2 year −1 and decreased CH 4 emission by 4 ± 4 g CH 4 m −2 year −1 , thus accumulating less C over 100 years (0.2 ± 0.2 kg C m −2 ). Yet, the reduced emission of CH 4 , which has a larger greenhouse warming potential, resulted in a net decrease in greenhouse gas balance by 310 ± 360 g CO 2‐eq m −2 year −1 . Peatlands with the initial WT close to the soil surface were more vulnerable to C loss: Non‐permafrost peatlands lost >2 kg C m −2 over 100 years when WT is lowered by 50 cm, while permafrost peatlands temporally switched from C sinks to sources. These results highlight that reductions in C storage capacity in response to drying of northern peatlands are offset in part by reduced CH 4 emissions, thus slightly reducing the positive carbon climate feedbacks of peatlands under a warmer and drier future climate scenario.